Dental markers of biocultural sex differences in an early modern population from Gothenburg, Sweden: caries and other oral pathologies - Bertilsson, Carolina; Nylund, Lisa; Vretemark, Maria; Lingström, Peter (BMC Oral Health, 2021)
With the aim to study dental pathological lesions in an early Swedish modern population, with special reference to sex variances of dental caries, the prevalence and distribution of dental caries and tooth wear were determined in complete and partial human dentitions from an early modern-time city graveyard (1500–1620) excavated in Gamlestaden, Gothenburg, Sweden.